2007
DOI: 10.1002/ptr.2217
|View full text |Cite
|
Sign up to set email alerts
|

A 90 day repeated oral toxicity study on plantamajoside concentrate from Plantago asiatica

Abstract: Plantago asiatica is distributed widely in East Asia. Since ancient times it has been used as a diuretic to treat acute urinary infections, and as an antiinflammatory, antiasthmatic, antioxidant, antibacterial, antihyperlipidemic and antihepatitis drug. The major compound, plantamajoside from P. asiatica, which is used as a marker compound in chemotaxonomic studies, was reported to have antibacterial activity, inhibition activity against cAMP phosphodiesterase and 5-lipoxygenase and antioxidant activity. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…A previous report discussed the isolations of plantamajoside, plantagin and aucubin from P. asiatica, as well as the various biological properties of these compounds, including antibacterial, antiallergic, antiinflammatory, antioxidative and lipoxygenase inhibitory activity (Nishibe, 2002). In our previous study, plantamajoside was isolated, and a 90 day repeated oral toxicity test was performed in rats, confirming its safety at a dose of 2000 mg/kg (Park et al, 2007). The purpose of the present study was to investigate the genotoxicity of plantamajoside, to further confirm its safety for use as a phytochemical agent in health products.…”
Section: Introductionmentioning
confidence: 69%
“…A previous report discussed the isolations of plantamajoside, plantagin and aucubin from P. asiatica, as well as the various biological properties of these compounds, including antibacterial, antiallergic, antiinflammatory, antioxidative and lipoxygenase inhibitory activity (Nishibe, 2002). In our previous study, plantamajoside was isolated, and a 90 day repeated oral toxicity test was performed in rats, confirming its safety at a dose of 2000 mg/kg (Park et al, 2007). The purpose of the present study was to investigate the genotoxicity of plantamajoside, to further confirm its safety for use as a phytochemical agent in health products.…”
Section: Introductionmentioning
confidence: 69%
“…such as ursolic acid, plantamajoside R, aceteoside R and plantagonin have been shown to have both an antioxidant and antiinflammatory effect [6]. Numerous studies have shown that Plantago species had a high phenolic content and antioxidant activity [39][40][41][42][43][44][45][46][47][48]. There are few studies carried out in Turkey showing high antioxidant activity for P. lanceolata [40][41][42][43][44][45][46][47][48][49][50] and P. major [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were processed, sectioned, and stained, with hematoxylin and eosin, and were examined by a pathologist. [6–9]…”
Section: Methodsmentioning
confidence: 99%